FACTORS DRIVING DECISION MAKING FOR PURCHASING HALAL PRODUCTS IN INDONESIA: LITERATURE REVIEW - Nurfahmiyati; Allya Roosallyn Assyofa; Kania Nurcholisah (UPT Publikasi Ilmiah UNISBA, 2023)
There has been an increase in consumer demand for halal products in recent year that does not only come from Muslim consumers but also from non-Muslim consumers. They view halal products as safe and healthy. This triggers consumer awareness of halal products and is followed by the wishes of producers to fulfill their rights to halal products. This research examines factors that drive purchasing decisions for halal products in Indonesia through a literature review. The findings of this research show there are several factors that determine someone’s decision to purchase halal products, i.e., religiosity, halal label, halal lifestyle, product knowledge, and Islamic branding/advertising. Keywords: Halal, Halal products, Indonesia, Purchase decision.